(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Preterm deliveries contribute to major morbidity and mortality in developing countries. They are a leading cause of admission in neonatal care units. It is a major hindrance to the attainment of the Sustainable Development Goal (SDG)-3 targets given its high contribution to neonatal mortality. Early detection of its risk factors and advances in the management have ensured better survival of preterm births. This study was conducted to determine the prevalence, underlying causes, morbidity patterns and outcome of preterm admissions to a neonatal intensive care unit (NICU) of a tertiary care center in Combined Military Hospital (CMH) Sylhet. Material and Methods: A descriptive study was conducted in CMH Sylhet from July 2018 to June 2020. All live preterm babies delivered at CMH Sylhet during the study period were included. Information obtained included gestational age at birth, gender, cause for preterm birth, problems during admission and outcome. Results: During this period, a total of 662 neonates were admitted out of which 107 (16.2%) were preterm with gestational ages ranging from 27 completed weeks to less than 37 completed weeks with a mean gestational age 33.2 weeks (± 2.7 weeks) and birth weights from 800 - 2600 gm with a mean of 2100 gm (± 700 gm). There were 52 males and 55 females (M: F 0.95). One hundred and thirty three (20.1%) were delivered by normal vaginal delivery while 529 (79.9%) were delivered by Caesarean section. The duration of hospital stay ranged from 1 - 45 days, with a mean duration of 15 days (± 9.2 days). The commonest reason for prematurity was premature rupture of membrane (PROM) (39.3%) followed by gestational diabetes mellitus (GDM) (35.5%), hypertensive disorders in pregnancy (30.8%), multiple pregnancy (29.9%) and inadequate ante natal care (ANC) (20.6%). The commonest morbidity in the patients in the present study was neonatal jaundice (90.7%) followed by respiratory problems (78.5%), sepsis (17.8%) and congenital heart disease (CHD) (15.9%). Case fatality rate for patients with respiratory distress syndrome (7.7%) and sepsis (5.3%) were common. Overall survival rate was 91.6% and was significantly (p <0.001) higher in the moderate to late preterm category compared to the very preterm and extremely preterm births. Conclusion: PROM, GDM, hypertensive disorders in pregnancy, multiple pregnancy and inadequate ante natal care were significantly associated with preterm birth. Neonatal jaundice, respiratory problems, sepsis and CHD were common morbidities observed. Case fatality rate was significant in neonates with respiratory distress syndrome and sepsis and overall survival rate was 91.6%. So, at-risk mothers should receive intensified antenatal care to mitigate preterm birth. J Bangladesh Coll Phys Surg 2022; 40: 39-44